(untitled) (Innovative professional education, 2023)
The article focuses on the professional competence of the college teacher, its components, namely: scientific competence in the subject; psychological-pedagogical, methodical, didactic competence in educating students; cultural, environmental, vocational, social, legal, political; competence in self-improvement. The essence of the professional competence of a teacher of a vocational college and its structural components have been determined.